Pengaruh Rasio Keuangan Terhadap Harga Saham Syariah Dengan Earning Per Share Sebagai Variabel Moderating - Muhammad Yusuf; Jefriyanto Jefriyanto (ITB AAS INDONESIA Surakarta, 2021)
This research is using secondary data obtained from the official website of IDX and Investing. Total population in this study are all JII members companies from 2016-2018 and the number of samples in this study are 18 companies that are members of the Indonesia Stock Exchange, especially in the Jakarta Islamic Index from 2016-2018. Data analysis techniques used in this study are the classic assumption test and the Moderated Regression Analysis (MRA) analysis test or commonly called the interaction test. Based on the results of the research conducted obtained the results of variables that have partial significant effect are DER, DPR, ROA, PBV while other variables such as PER, CR, NPM and DYR has no effect on sharia stock prices. Then for the moderation variable (Earning Per Share) proved able to moderate each independent variable and this moderating variable can strengthen the relationship between the independent variable (X) to the dependent (Y).